Exploring inequalities in survival after out-of-hospital cardiac arrest in Scotland - Bijman, Laura Anna Emma (My University, 2025)
INTRODUCTION: Out-of-hospital cardiac arrest (OHCA) remains a serious, worldwide health issue. Recent research highlights that there are inequalities in survival after OHCA. These inequalities could be related to sex, age, socio-economic status, race, geographical location of OHCA among other variables. Unfortunately the majority of health research is still performed on middle-aged white males living in socio-economic affluent areas. This makes inequalities in healthcare outcomes structurally underexposed. The overall aim of this thesis was to investigate whether inequalities in outcomes after OHCA exist in Scotland. Furthermore I am interested in factors possibly explaining inequalities in outcomes after OHCA. METHODS: For all analyses in this thesis data from 20,585 adult, non-Emergency Medical Services (EMS)-witnessed OHCA cases where resuscitation was attempted by EMS was used. I included cases from the whole of Scotland between April 1, 2011 and March 1, 2020. For the systematic review focusing on sex and outcomes after OHCA an extensive literature search was performed. Subsequently two meta-analyses, one with unadjusted odds ratios (ORs) and one with adjusted ORs, were conducted to identify and critically appraise existing studies looking into the association between sex and survival after OHCA. As mentioned in the introduction, this thesis focuses on the association between the sex, socio-economic status, geographical location and subsequent survival after OHCA. The methods used for all analyses included in this thesis were logistic regressions analyses using 30 days survival after OHCA as the outcome. In all analyses potential confounding variables were taken into account. Additional mediation analyses to identify explanatory variables for the association between sex and geographical area and subsequent OHCA survival were undertaken. In some chapters appropriate stratified analyses and sensitivity analyses were included. RESULTS: The results from the systematic review showed that a possible explanation for the conflicting results of previous systematic reviews investigating the association between sex and survival after OHCA lays in the fact that they combined studies that showed crude results and studies with confounder adjusted results. Based on these observations I completed a systematic review focusing on sex and survival after OHCA. A priori, I decided to pool the results from crude and confounder adjusted analyses separately. The pooled results of the crude results (N=23) indicated that males have a higher chance of survival after OHCA than females. In contrast, the meta-analysis (N=10) including confounder adjusted results indicated no sex difference in survival after OHCA. Logistic regression using our own Scottish OHCA registry data showed the same results. Males had higher age-adjusted 30-day survival after OHCA than females. However, after adjusting for confounding/mediating variables, sex was not associated with 30-day survival after OHCA. My study identified initial cardiac rhythm (ICR) as a potential mediating variable of higher 30-day OHCA survival in males than females. Investigating the association between socio-economic status and survival after OHCA I conducted crude logistic regression analysis. This analysis showed lower odds of 30-day survival in the most deprived areas compared with the least deprived areas. Adjustment for age, sex, and urban-rural location decreased the relative odds of survival in the most deprived areas further. Age stratified analyses demonstrated the most pronounced association to be among young males. Across the quintiles of increasing deprivation, decreasing trends in the proportion of those presenting with shockable ICR and those receiving bystander cardiopulmonary resuscitation (bCPR) were found. Furthermore, I conducted logistic regression analyses to assess the association between urban-rural incident locations and 30-day survival after OHCA. These analyses showed people experiencing OHCA in urban areas were 19% more likely to survive to 30-days than people in rural areas (adjusted for age, sex and socio-economic status). Long EMS arrival time, which was more prevalent among rural areas, was identified as a mediating variable. CONCLUSIONS: This thesis showed that inequalities in 30-day survival following OHCA are a public health issue in Scotland. I addressed several shortcomings of the existing evidence base. This research suggested that it is unlikely that biological sex itself is associated with 30-day survival after OHCA. However, survival percentages after OHCA are still higher in males than females. Our research suggests that this survival percentage difference between males and females may be explained by sex-differences in presenting with a shockable ICR. A higher percentage of males present with shockable ICR and females are more likely to experience OHCA at home. This thesis also identified inequalities in socio-economic status and 30-day survival following OHCA. People living in the most affluent areas of Scotland are more likely to survive to 30-days after OHCA compared with people living in the most deprived areas of Scotland. This difference was not explained by confounding due to age, sex or urban-rural location. Differences in urban-rural geographical locations of OHCA are also identified as an inequality in this thesis. Urban OHCA incident locations are associated with higher 30-day survival after OHCA compared with rural OHCA incident locations. Early EMS arrival time (a probable proxy for time to first defibrillation) was identified as a likely mediator. Further research could investigate how the proportion of females who present with shockable ICR can be increased to decrease the male-female 30-day survival gap following OHCA. For example by focusing on how bCPR rates in females could be improved. To improve EMS (defibrillator) arrival times in rural areas in Scotland, future research could try to identify which areas would benefit most from approaches such as crowd-sourcing bystander help via a smartphone app or the use of trained community responder volunteers.
Keywords: Inequalities; Survival; OHCA (Out-of-hospital cardiac arrest); Sex differences; Socio-economic status